Striving towards integrated people-centred health services: reflections on the Australian experience - Legge, David G (Fam Med Community Health, 2019)
Health systems around the world are under continuing pressure for reform. Health system reform involves both content and process. Content deals with changes to the structures of the health system; process deals with the strategies of change. In this paper, we reflect on the development of the Australian healthcare system and draw out lessons regarding both structural and developmental principles. We review the historical development and functional performance of a range of ‘programmes’ which comprise the Australian health system. We use WHO’s 2016 ‘framework on integrated people‐centred health services’ as a standard against which to evaluate the performance of the different programmes. A model of health system development featuring incremental change, windows of opportunity and policy coherence is used to frame some lessons from the Australian experience regarding reform strategy. Several of the programmes reviewed can be shown to have contributed positively to integrated and people-centred services. However, there have also been significant shortfalls in performance. The successes and the shortfalls of the programmes reviewed reflect both their histories and their contemporary context. Structural principles emerging from this review include the policy leverage available under single payer purchasing and on the other hand the fragmenting effects of privatisation and marketisation. Lessons regarding strategies of reform include cultivating ‘reform readiness’ across all of the locations and levels where opportunities for change may emerge while cultivating system wide coherence through a shared vision of how the system as a whole should develop.